Guardians of letters : literacy, power, and the transmitters of early Christian literature - Haines-Eitzen, Kim (Oxford ; New York Oxford University Press, 2000)
Who were the scribes who copied early Christian literature during the second and third centuries? What roles did they play in the reproduction and dissemination of these writings? To answer these questions, this study uses evidence from early Christian literature and the earliest Christian papyri - including their form, physical features, and textual characteristics.
Keywords: Christian literature, Early -- Latin authors -- History and criticism. Transmission of texts -- Rome. Scribes -- Rome